Implementing Videos and Songs to Enhance Listening and Oral Skills in Third Graders (2021)
ABSTRACT : This action research project aimed to explore how videos and songs may improve third graders' listening and speaking skills in English at a public institution in Rionegro, Antioquia. I gathered the data through different instruments, including teacher journals, two surveys, two diagnostic tests, and a focus group. In general, findings suggested that young learners felt comfortable and engaged when using videos and songs to develop the English sessions. Likewise, their participation and self-confidence to pronounce the target lexis increased, and the aural-oral skills: listening comprehension and oral production boosted significantly during the implementation.